PERAN KEPALA SEKOLAH TERHADAP PENINGKATAN KOMPETENSI PROFESIONALITAS GURU PADA PROSES PEMBELAJARAN DI SDN 22 BENGKALIS - Ali Anas (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research was school action aiming to improve the school quality and the teachers’ performance. This research was conducted at SDN 22 X. The subjects in this study were the teachers who taught at the school. This research utilized a descriptive quantitative method that explained and described the facts found at the time of the research. The main purpose of this research was to improve and develop the teachers’ ability or professional competence in teaching to create good learning conditions, to produce good learning outcomes, and to improve the quality of education. Based on the results of the study, it was seen that the principal’s role was very crucial in developing and improving the teacher’s professional ability in teaching. It was supported by the data showing that the score of teachers’ mastery on the materials was 3 with “high” category. Then, the score of the ability to open lessons was 4 with “very high” category. After that, the score of the ability to ask questions was 3 with “high” category while the score of the ability to hold learning variations was 4 with “very high” category. Moreover, the score of the clarity of presenting the material was 3 with “high” category, and the score of the ability to manage the class was 4 with “very high” category. Thus, this research concluded that teacers’ professional ability increased as the result of the principal’s efforts to improve teaching process.